THE INFLUENCES OF KNOWLEDGE, BEHAVIOUR AND ATTITUDE IN SELECTING POWDER TYPE: THE INCIDENCE OF ACNE VULGARIS - Anggita Nur Fauzana; Indri Hapsari; Irsalina Nurul Putri; Githa Fungie Galistiani (Jurnal Farmasi Sains dan Praktis, 2022)
Acne vulgaris is a chronic obstructive and inflammatory skin disease. It occurs in almost all adolescents with a prevalence of 90%. Powder is the most widely used cosmetic in the long term and one of the causes of Acne vulgaris which causes occlusion of pores on the skin surface. The purpose of this study was to analyze the effect of the level of knowledge, attitudes and behavior of choosing the type of powder on the incidence of acne vulgaris in Banyumas Regency. This study was an observational study with data collection techniques using cluster sampling and sampling technique by accidental sampling. The level of knowledge of women in the Banyumas Regency was dominated by the high category as many as 64 respondents (64.0%). The incidence of acne vulgaris out of 100 respondents, 67 (67.0%) of respondents had mild acne vulgaris, 22 respondents (22.0%) had moderate acne vulgaris and 1 respondent (1.0%) had severe acne vulgaris and the rest had no acne vulgaris. Chi-square analysis showed that there was a relationship between knowledge with behavior and attitude in choosing the type of powder to the incidence of acne vulgaris as evidenced by the p value of each variable, namely 0.044 and 0.028 (p <0.05). The level of knowledge with behavior and attitude in choosing the powder type had a significant relationship to the incidence of acne vulgaris in women in Banyumas Regency.